An econophysics approach to study the effect of BREXIT referendum on European Union stock markets - Guedes, Everaldo (2019)
We analyze the auto-correlations of all European Union (EU) indices and the crosscorrelation between the UK stock market and the other EU markets. This analysis took into account the BREXIT referendum, on the 23rd of June 2016 and the entire period was partitioned in two periods, before and after the BREXIT referendum. First of all, we applied the Detrended Fluctuation Analysis method (with the regular and with a sliding windows approach) in order to evaluate market efficiency. In this case, we found that in general the referendum did not change efficiency levels significantly. With the main purpose of measuring the markets interdependence in relation to the UK index, following the referendum, we calculated the ΔρDCCA coefficient. Our results point to a decrease in the cross-correlation coefficient (ΔρDCCA < 0), meaning that the UK is more segmented now, in relation to other EU partners, than in the past. With ΔρDCCA it was possible to identify how much the referendum influenced the interdependence, but not the efficiency, of European markets.